2022
DOI: 10.3389/fonc.2022.953920
|View full text |Cite
|
Sign up to set email alerts
|

Safety, feasibility, and application of intraperitoneal gas-based hyperthermia beyond 43°C in the treatment of peritoneal metastasis: An in-vivo pilot study

Abstract: Background43°Celsius (C) is currently the highest temperature used in the treatment of peritoneal metastasis (PM). Despite sufficient data on water- based hyperthermic solutions in PM treatment, there is currently no information on gas-based hyperthermia extending beyond 43°C. This study is the first to provide in-vivo data on different organ systems during and after intraperitoneal gas-based hyperthermia beyond 43°C. The aim of this study is to explore in-vivo feasibility, safety, and efficacy of this novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The cytotoxic effects of chemotherapy on cancer cells are further enhanced by partially dehydrating the cells in a hyperthermic environment. The concept of feasibility of such an approach has already been demonstrated in vivo [ 35 , 36 , 37 ]. For the first time, we have now investigated the combination of all three therapeutic factors—hyperthermia, dehydration, and chemotherapy—as a possible procedure for PM treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The cytotoxic effects of chemotherapy on cancer cells are further enhanced by partially dehydrating the cells in a hyperthermic environment. The concept of feasibility of such an approach has already been demonstrated in vivo [ 35 , 36 , 37 ]. For the first time, we have now investigated the combination of all three therapeutic factors—hyperthermia, dehydration, and chemotherapy—as a possible procedure for PM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The application of hyperthermia through a gas-based system instead of a liquid-based carrier has a higher likelihood of improvement following laparoscopy. Previous in vivo swine model studies carried out by our research group showed that gas-based intraperitoneal hyperthermia is well tolerated and safe for these animals, and in vitro studies indicate cytotoxic effects on colorectal cancer cell lines, suggesting that this method could be used as a potential tool in PM treatment [ 35 , 36 ]. Based on this, the now presented data is a further indication that combining gas-based hyperthermia with chemotherapy is more cytotoxic on colorectal cancer cells and therefore could also potentially have an additive antitumoral effect in the management of PM than locoregional chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations